LEADERSHIP, SUSTAINABLE DEVELOPMENT AND STRATEGIC MANAGEMENT OF INNOVATIVE BUSINESS: CHALLENGES AND PROSPECTS FOR STARTUPS - VOVK, Mykola; BONDARENKO, Yurii; HONTOVYI, Denys; DENYSENKO, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the interrelation between leadership, sustainable development, and strategic management in innovative business, emphasizing their decisive role in shaping the competitiveness and long-term stability of startups. It is substantiated that in the modern globalized economy, startups serve as key drivers of innovation, technological progress, and digital transformation. Their success increasingly depends on the ability of leaders to combine strategic vision with social responsibility, adaptability, and innovative thinking. Leadership is viewed as a multidimensional phenomenon that integrates strategic foresight, communication competence, and the ability to inspire teams to achieve shared goals. The paper highlights that an effective startup leader acts not only as a manager but also as a visionary, mentor, and motivator capable of building an organizational culture that supports creativity and sustainability. Particular attention is paid to the importance of emotional intelligence, empathy, and ethical decision-making in strengthening trust and cohesion within startup teams. The study analyzes the main challenges facing innovative enterprises, including financial constraints, market uncertainty, rapid technological change, and the growing need for environmental and social accountability. It is demonstrated that integrating the principles of sustainable development and ESG (Environmental, Social, Governance) management into startup strategies enhances resilience, reduces operational risks, and contributes to building a positive corporate reputation. The article proposes strategic directions for strengthening startups’ innovative capacity: digital transformation of management processes, partnership development within innovation ecosystems, investment in human capital, and formation of sustainable business models focused on long-term value creation. The research results expand the theoretical foundations of strategic management in innovative entrepreneurship and offer practical tools for improving startup performance in dynamic and uncertain business environments.
Keywords: leadership; sustainable development; strategic management; startups; innovation